2017
DOI: 10.3945/ajcn.117.153338
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption after myocardial infarction and risk of cardiovascular mortality: a prospective analysis in the Alpha Omega Cohort

Abstract: Consumption of coffee, one of the most popular beverages around the world, has been associated with a lower risk of cardiovascular and all-cause mortality in population-based studies. However, little is known about these associations in patient populations. This prospective study aimed to examine the consumption of caffeinated and decaffeinated coffee in relation to cardiovascular disease (CVD) mortality, ischemic heart disease (IHD) mortality, and all-cause mortality in patients with a prior myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
1
22
0
3
Order By: Relevance
“… 13 Conversely, in a Dutch population, the Alpha Omega Study involving 4837 patients with prior myocardial infarction determined that consuming more than four cups/day of coffee increased mortality by 24% in diabetic patients, whereas it decreased mortality by 27% in those without diabetes. 14 In the Nurses’ Health Study (7170 female patients with diabetes), habitual coffee consumption was not found to be associated with increased risk of mortality. 18 The UK Biobank (total n=498 134 participants) failed to identify a significant association between coffee consumption and mortality in diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 13 Conversely, in a Dutch population, the Alpha Omega Study involving 4837 patients with prior myocardial infarction determined that consuming more than four cups/day of coffee increased mortality by 24% in diabetic patients, whereas it decreased mortality by 27% in those without diabetes. 14 In the Nurses’ Health Study (7170 female patients with diabetes), habitual coffee consumption was not found to be associated with increased risk of mortality. 18 The UK Biobank (total n=498 134 participants) failed to identify a significant association between coffee consumption and mortality in diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“… 19 The difference may be explained by coffee having harmful effects among patients at higher CVD risk: that is based on findings that higher coffee consumption increased mortality among diabetic patients with previous myocardial infarction. 14 Japanese type 2 diabetes patients are generally at lower CVD risk than developed ones: 20 thus, caffeine may exert less detrimental effects on the vasculature, resulting in enhanced beneficial effects of coffee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between coffee or tea consumption and CHD or lipid profiles is still not well studied, and previous epidemiological study results draw different conclusions (40)(41)(42)(43)(44)(45)(46)(47) . Previous studies reported that coffee or tea consumption is inversely associated with CHD or serum lipids (40,41) .…”
Section: Discussionmentioning
confidence: 94%
“…Although caffeine consumption appears to be associated with a decreased risk of developing type 2 diabetes, it is unclear if its protective effect persists in people with established diabetes. In a prospective study including 4,365 patients with a prior myocardial infarction, drinking coffee was associated with lower risk of cardiovascular mortality and ischemic heart disease mortality ( 9 ). In this study, significant inverse associations were reported in patients without diabetes, whereas the associations were weak and non-significant in the smaller group with diabetes.…”
Section: Introductionmentioning
confidence: 99%